Sistem Informasi Pemasaran Hasil Bumi Berbasis Web - Erwin Gatot Amiruddin (Celebes Computer Science Journal, 2020)
This study was conducted to reduce the losses are always experienced by farmers because of the behavior of the middlemen who are not responsible for always playing the market price of agricultural and plantation. Implementation of this research using smart devices, and create a marketing information system application named crops crop prices. Implementation of the application price of the plant is also used to provide marketing information to farmers crops to reduce losses due to price games conducted by the middlemen who are not responsible. From the results of this study indicate that the information the application provides convenience for farmers to obtain agricultural produce marketing information and applications are already well underway.